(untitled) (Experimental biology, 2009)
A method for the microclonal propagation of modern shrub rose cv. ‘Alaska’ was developed. Apex explants from in vitro young shoots were excised and cultured on basal medium of Murashige and Skoog (1962, MS) containing several concentrations of BAP, NAA and kinetin. Multiple shoot formation of up to 3 shoots was obtained on MS medium supplemented with 0,5 mg/l BAP. Shoot readily rooted on ½ MS medium added with 0,5 mg/l IAA and 1,0 mg/l IBA.